Model simulation suitable for an aircraft at high angle of attack - Mohmad Rouyan, Nurhana (Cranfield University, 2016)
Simulation of a dynamic system is known to be sensitive to various factors and one of them could be the precision of model parameters. While the sensitivity of flight dynamic simulation to small changes in aerodynamic coefficients is typically not studied, the simulation of aircraft required to operate in nonlinear flight regimes usually at high angles of attack can be very sensitive to such small differences. Determining the significance and impact of the differences in aerodynamic characteristics is critical for understanding the flight dynamics and designing suitable flight control laws. This thesis uses this concept to study the effect of the differences in aerodynamic data for different aerodynamic models provided for a same aircraft which is F-18 HARV combat aircraft. The aircraft was used as a prototype for the high angles of attack technology program. However modeling an aircraft at high angles of attack requires an extensive aerodynamic data which are usually di cult to access. All aerodynamic models were collected from open literature and implemented within a nonlinear six degree of freedom aircraft model. Inspection of aerodynamic data set for these models has shown mismatches for certain aerodynamic derivatives, especially at higher angles of attack where nonlinear dynamics are known to exist. Nonlinear simulations are used to analyse three different types of flight dynamic models that use look-up-tables, arc-tangent formulation and polynomial functions to represent aerodynamic data that are suitable for high angles of attack application. To achieve this, a nonlinear six degree of freedom Simulink model was developed to accommodate these aerodynamic models separately. The trim conditions were obtained for different combinations of angles of attack and airspeed and the models were linearized in each case. Properties of the resulting state matrices such as eigenvalues and eigenvectors were studied to determine the dynamic behaviour of the aircraft at various flight conditions.
Keywords: NASA F-18 HARV; High angles of attack; Aerodynamic model; Aircraft simulation